Effect of irrigation and nitrogen on growth, yield and water-use efficiency of black cumin (Nigella sativa) in lower Indo-Gangetic plains - GOSWAMI, S B (The Indian Journal of Agricultural Sciences, 2011)
An experiment was conducted during winter (rabi) season of 2005–06 and 2006–07 to find out the differential irrigation and nitrogen management effects on black cumin (Nigella sativa) in alluvial plains of West Bengal. Irrigation based on soil moisture tension at ψm= –0.03 at 20 cm soil depth recorded the maximum seed yield of 445 kg/ha wherein crop received four irrigations with an interval of 18–20 days. The highest seed yield (412 kg/ha) recorded with 80 kg N/ ha was significantly superior to 20, 40, and 60 kg/ha, respectively. Actual evapotranspiration (AET) of black cumin was low (181 mm) under limited water supply situation but irrigation at ψm = - 0.03 MPa recorded the maximum AET of 272 mm. The high dose of 80 kg N/ha increased the AET value to the extend of 225 mm and increment in N level increased the AET. Water-use efficiency (WUE) was recorded maximum (1.81 kg/ha/mm) when crop was under moderately wet moisture regime (ψm = –0.05 MPa), whereas WUE value decreased with increased water supply at ψm = –0.03 MPa in black cumin. Irrigation and nitrogen management improved the benefit:cost ratio of the crop by 14.8– 18.7%. In black cumin, irrigation at ψm= –0.03 MPa, ie irrigation at an interval of 18–20 days with a nitrogen dose of 80 kg/ha was found equally productive and economic in the sandy loam soils of Indo-Gangetic plains.